EVALUATING FINANCIAL HEALTH OF GUJARAT STATE FERTILIZERS THROUGH ‘Z’ SCORE MODEL - Saini, Vikash (International Journal of Research -GRANTHAALAYAH, 2018)
The evaluation of financial health is very useful for financial managers, investors and other users. In this study it is tried to know whether Z score model is able to evaluate financial health of Chambal Fertilizers and Chemicals ltd for past 10 years (2007-08 to 2016-17). Analysis of this paper shows that the model is useful to know the financial soundness of Chambal Fertilizers. In this paper overall results of Z score model indicating that the financial position of the corporation is on alert to exercise the caution. These result shows that Altman model can give good analysis for fertilizers sector in India. Hence it can be concluded that user of financial statements like financial managers, analysts, investors etc can predict business failure or financial soundness of companies through Altman Z score model.